2023
DOI: 10.1021/acscatal.2c06158
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Performance Descriptor in Direct Syngas Conversion to Long-Chain α-Olefins over Ruthenium-Based Catalysts Promoted by Alkali Metals

Abstract: Fischer-Tropsch synthesis (FTS) provides a nonpetroleum route for the production of value-added α-olefins from syngas. However, regulating the product distribution to promote the formation of long-chain α-olefins while maintaining low selectivity to C1 byproducts (CO 2 and CH 4 ) remains a great challenge. Herein, a series of alkali metal-promoted Ru/SiO 2 catalysts were synthesized to investigate the effect of alkali metals and identify the performance descriptor for syngas to α-olefins. Xray absorption and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The catalytic performance of the Ru/TiO 2 catalyst with two crystal phases of TiO 2 support was evaluated at 1 MPa, 3000 mL g −1 h −1 , H 2 /CO = 2 and 260 °C. Before reaction, the catalysts were reduced with pure H 2 at 300 °C for 4 h. Since prior work suggested that Na plays a crucial role in shifting the product selectivity of a metallic Ru-based catalyst from paraffins to olefins during CO hydrogenation, 7,21 most catalysts described here contained an Na promoter with a fixed weight ratio Na/Ru of 0.1. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic performance of the Ru/TiO 2 catalyst with two crystal phases of TiO 2 support was evaluated at 1 MPa, 3000 mL g −1 h −1 , H 2 /CO = 2 and 260 °C. Before reaction, the catalysts were reduced with pure H 2 at 300 °C for 4 h. Since prior work suggested that Na plays a crucial role in shifting the product selectivity of a metallic Ru-based catalyst from paraffins to olefins during CO hydrogenation, 7,21 most catalysts described here contained an Na promoter with a fixed weight ratio Na/Ru of 0.1. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 Subsequent work also suggests that the types of promoter and support could greatly affect the performance of Fischer-Tropsch synthesis to olefins (FTO) for supported Ru-based catalysts. 8,9 Tiejun Lin Tiejun Lin earned his BS degree from Zhejiang University of Technology and received his PhD degree in 2015 from East China University of Science and Technology. He then joined in Shanghai Advanced Research Institute (SARI), Chinese Academy of Science (CAS), where he was promoted to full professor in 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the catalytic performance of Co-based heterogeneous catalysts for hydroformylation, various noble metals are always added. 17,18 In addition, the promotion effect of alkali metals as electron promoters or structural promoters has received great attention, which has shown extensive applications in many reactions such as ammonia synthesis, 19 Fischer–Tropsch synthesis, 20,21 aromatic hydrocarbon conversion, 22 and carbon dioxide hydrogenation. 23,24 As electronic modification agents, alkali metals can induce the formation of specific active centers (such as M δ + cations 25 and carbide phases 26 ) and regulate the adsorption/activation of reactants and intermediates, thereby modulating catalytic activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alkali metals are frequently employed as promoters with a strategic inclusion of minute quantities for iron-based catalysts in FTS processes, while they exert a significant improvement on the performances of FTS by leading to a boosted yield of olefins. Among the various alkali metals, soduim (Na) was most widely used due to its remarkable effects on the reactivity of iron-based catalysts toward FTS, and two possible mechanisms are suggested in terms of the structure–reactivity relationship between Fe-based catalysts and FTS. For one thing, the presence of Na was considered to improve the generation of the active phase of iron carbide which serves as the active site for olefin production in FTS according to the linear relationship between the amount of iron carbide and olefin yield. For the other, the Na dopant is also regarded as an electronic promoter, which could modulate the catalytic behavior of Fe active sites. , In this case, the electron transfer from Na to Fe-based active sites is considered, which thus leads to a preferred reaction route toward olefin desorption from catalyst surfaces.…”
Section: Introductionmentioning
confidence: 99%